Determinants of loan repayment performance of household and micro borrowers in Vietnam - Phạm, Thanh Dung (2020)
Vietnam is a developing economy where the service industry and light industry account for a big percentage of businessesin the economy. Businesses in these sectors are almost small and micro enterprises and household/family businesses (MSEs). They are always in need of capital for their activities. However, it’s very difficult for them to get access to loans from banks and credit organizations. Because they almost don’t have collateral to secure for their loan and are not able to provide an eligible financial statement which isusually required by banks. Consequently, banks or creditors are not interested in offering loan to such clients because they usually don’t have collaterals and have difficulties in providing documents as required by banks, which is very risky toabank if they accept such typesof customers, whereas, there are not enough tools to define and mitigate relevant risk. It’s very difficult for them to determine whichare key factors affecting on loanrepayment performance of micro-businesses in Vietnam, especially when using cash in payment is still popular, which makesbanks find it more difficult and not interested in loans for micro business. So, detailed research on the determinants of loanrepayment performance of micro-businesses in Vietnam is essential. The objectivesof this research is to analyze the determinants of credit risk of loanrepayment performance of micro-businesses in Vietnam